SCHEME OF STUDYING FUNCTIONS FOR MONOTONICITY AND EXTREMUM - Sabohat Eshmetova; Mamatqobil Esonturdiyev (Web of Journals Publishing, 2024)
The article discusses the scheme of studying a function for monotonicity and extremum
Keywords: scheme, study, function, monotonicity, extremum.